Racket trajectories of tennis stroke for drive volley and drive groundstroke - Tai, M. L.; Cheng, H. W.; Yang, C. J.; Lin, Y. C.; Tang, W. T.; Chen, Y. L.; Hsiao, S. Y.; Hsu, H. E. (14th International Symposium on 3D Analysis of Human Movement, 2016)
The purpose of this study was to compare the female player's characteristics of the velocity of the racket hitting trajectory, the racket head velocity, and the racket face angle between drive volley ball and grown stroke during impact. The subjects were five outstanding female tennis players who hold racket with two hands in backhand hitting. The tests were carried out in a standard size tennis court, and we use ten Eagle cameras with high-speed infrared camera (capture frequency of 200Hz) to collect all the image information. The results showed that (1) at the impact, the horizontal (x) velocity of the ground stroke is greater than drive volley, but there was no significant different between these two styles. The vertical (z) velocity of the racket head of drive volley was significant greater the ground stroke. (2) at the impact, the face angle of drive volley is significant smaller (83.85±2.12) then ground stroke (93.85±2.82). (3) the racket head displacement on x-axis and z-axis at 0.1 and 0.2 second before and after impact of ground stroke and drive volley, but there was no significant different between these two styles.